Cooperative Binding of Substrate and Ions Drives Forward Cycling of the Human Creatine Transporter-1 - Farr, Clemens V.; El-Kasaby, Ali; Erdem, Fatma A.; Sucic, Sonja; Freissmuth, Michael; Sandtner, Walter (Frontiers in Physiology, 2022)
Creatine serves as an ATP buffer and is thus an integral component of cellular energy metabolism. Most cells maintain their creatine levels via uptake by the creatine transporter (CRT-1, SLC6A8). The activity of CRT-1, therefore, is a major determinant of cytosolic creatine concentrations. We determined the kinetics of CRT-1 in real time by relying on electrophysiological recordings of transport-associated currents. Our analysis revealed that CRT-1 harvested the concentration gradient of NaCl and the membrane potential but not the potassium gradient to achieve a very high concentrative power. We investigated the mechanistic basis for the ability of CRT-1 to maintain the forward cycling mode in spite of high intracellular concentrations of creatine: this is achieved by cooperative binding of substrate and co-substrate ions, which, under physiological ion conditions, results in a very pronounced (i.e. about 500-fold) drop in the affinity of creatine to the inward-facing state of CRT-1. Kinetic estimates were integrated into a mathematical model of the transport cycle of CRT-1, which faithfully reproduced all experimental data. We interrogated the kinetic model to examine the most plausible mechanistic basis of cooperativity: based on this systematic exploration, we conclude that destabilization of binary rather than ternary complexes is necessary for CRT-1 to maintain the observed cytosolic creatine concentrations. Our model also provides a plausible explanation why neurons, heart and skeletal muscle cells must express a creatine releasing transporter to achieve rapid equilibration of the intracellular creatine pool.